Effects of Sonchus asper and apigenin-7-glucoside on nociceptive behaviors in mice - Mohammad Zarei; Saeed Mohammadi; Siamak Shahidi; Ali Reza Fallahzadeh (GarVal Editorial Ltda., 2017)
Context: Sonchus asper is an important herbal medicine that traditionally used to treatment of digestive system infections and heart disease. Aims: To evaluate of anti-inflammatory and antinociceptive effects of Sonchus asper hydroalcoholic leaf extract (SALE) and one of its major constituent, apigenin-7-glucoside (Ap7G), in male mice. Methods: In this experimental studies were used nociceptive assessment tests, which include writhing, tail-flick, and formalin-, and glutamate-induced paw licking tests. In addition, xylene test was used for evaluating of anti-inflammatory effect of SALE and Ap7G. Results: In tail-flick, writhing and glutamate-induced paw licking tests, application of a dose of 300 mg/kg of extract showed significantly (p<0.01) antinociceptive effect compared to the control group. In the formalin test, treatment with a dose of 100 mg/kg of extract reduced the pain scores in the tonic phase compared with the control group (p<0.05). In formalin model, also naloxone (an opioid non-selective antagonist) plus the extract (300 mg/kg) reduced licking and biting in mice. Moreover, the use of morphine decreased the nociceptive activity in all assessment tests. In addition, in xylene test, treatment with dose of 100 mg/kg of SALE increased the inhibition (49%) comparing to the control group. The Ap7G showed significant antinociceptive and anti-inflammatory effects in all tests. Conclusions: SALE and Ap7G have both antinociceptive and anti-inflammatory effects under the experimental conditions performed in this study. The modulation of the glutamatergic system by opioid receptors could be involved, at least in part, in these effects.